2008
DOI: 10.1111/j.1365-2478.2007.00718.x
|View full text |Cite
|
Sign up to set email alerts
|

Diffraction imaging in depth

Abstract: A B S T R A C THigh resolution imaging is of great value to an interpreter, for instance to enable identification of small scale faults, and to locate formation pinch-out positions. Standard approaches to obtain high-resolution information, such as coherency analysis and structure-oriented filters, derive attributes from stacked, migrated images. Since they are image-driven, these techniques are sensitive to artifacts due to an inadequate migration velocity; in fact the attribute derivation is not based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(42 citation statements)
references
References 25 publications
(53 reference statements)
0
38
0
Order By: Relevance
“…However, zero-offset stacking requires an accurate velocity analysis and special stacking procedures to preserve diffracted events. Moser and Howard (2008) showed that the conventional normal moveout stack may remove information about diffractions due to the different moveouts between diffracted and reflected waves. One possibility for obtaining a zero-offset approximation while preserving the diffracted energy is to use the path summation technique, which optimally stacks coherent events with all possible stacking velocities (Landa et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, zero-offset stacking requires an accurate velocity analysis and special stacking procedures to preserve diffracted events. Moser and Howard (2008) showed that the conventional normal moveout stack may remove information about diffractions due to the different moveouts between diffracted and reflected waves. One possibility for obtaining a zero-offset approximation while preserving the diffracted energy is to use the path summation technique, which optimally stacks coherent events with all possible stacking velocities (Landa et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Fomel et al (2007) use plane-wave-destruction filters to perform diffraction separation. From an imaging point of view, Moser and Howard (2008) use antistationary filtering to separate reflective and diffractive components during the migration, while Zhang (2004) performs prestack depth diffraction imaging using the idea of the Fresnel aperture. Diffraction enhancement can also be carried out using MF (Berkovitch et al, 2009) or the CRS (e.g., Asgedom et al, 2011b;Dell and Gajewski, 2011) stacking methods.…”
Section: Description Of Window-steered Musicmentioning
confidence: 99%
“…More recently, much attention has been paid to the enhancement and separation of diffractions from reflection data for many imaging purposes. Several approaches have been proposed, among them the use of antistationary filtering (Moser and Howard, 2008), plane-wave destruction filters (Fomel et al, 2007), multifocusing (MF) (Berkovitch et al, 2009), or the common reflection surface (CRS) (Asgedom et al, 2011a(Asgedom et al, , 2011b(Asgedom et al, , 2012a(Asgedom et al, , 2012b stacking methods. Because the diffracted events are known to carry high-resolution information about the subsurface, their optimal use in imaging is an important topic.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of diffractions in high-resolution structural imaging has been emphasized in many recent publications (Khaidukov et al, 2004;Kozlov et al, 2004;Fomel et al, 2006;Landa et al, 2008;Moser and Howard, 2008;Moser, 2009;Klokov et al, 2010;Dell and Gajewski, 2011;Koren and Ravve, 2011;Klokov and Fomel, 2012;Decker et al, 2013;Popovici et al, 2014;Sturzu et al, 2014), and diffraction imaging is emerging as a new tool in seismic interpretation. By careful preprocessing, the inherent redundancy of prestack seismic data can be used to separate the contribution of high-energy specular events from those of low-amplitude events scattered by local unconformities and heterogeneities.…”
Section: Introductionmentioning
confidence: 99%